The Effectfor Students Reading Comprehension Of Narrative Text With Applying 3-2-1strategy - M, Masturanada (Universitas Muhammadiyah Sumatera Utara, 2021)
The objective of thisresearch was to investigate the effect of applying 3-2-1 strategy on students reading comprehension of narrative text.This research applie dex perimental research. Population of this research is taken from eight grade of SMP Cerdas Murni Tembung academic year 2019/2020 with the total population 367 students. The researcher just took two class as the sample. The sample was taken byusing purposive sampling technique. The sample consisted of 38 students in classVIII-2. The experimental group was taught by applying 3-2-1 strategy on students reading comprehension of narrative text. While in class VIII-1 group sare taught using traditional methods in reading comprehension. The instruments of collecting data was multiple choice test which consisted of 20 items. The experimental group was given pre-test and post-test. After the data had been collected, these were analyzed by using t-test formula.Theres ulto fanalys is showed that-observe (to=5.929) was higher than t-table with the level of significant ?= 2,024. The final hyphothesis showed that Ho was rejected and Ha was accepted. It means that therewas a significant effect of applying 3-2-1 strategy on students reading comprehension of narrative text.